Team Based Learning Experience from a College of Pharmaceutical Sciences in United Arab Emirates - Rao, Padma GM; Rabbani, Syed Arman (Indian Journal of Pharmaceutical Education and Research, 2022)
Introduction: Team-Based Learning (TBL) is an active-learning methodology that has been successfully employed in various health schools’ curricula. This study assessed the perception of pharmacy students studying in a College of Pharmaceutical Sciences towards TBL with an emphasis on their perception to online TBL. Materials and Methods: The study was a cross sectional survey including students of all the four years of Bachelor of Pharmacy program. Team-based learning student assessment instrument (TBL-SAI) was used to evaluate the perception of pharmacy students towards TBL. Results: Out of the total 82 students, majority were female (n=52, 63.4%, 95% CI: 52.4 - 73.2) and were from final year of the program (n=38, 46.3%, 95% CI: 35.4 - 57.3). Mean age of the study participants was 21.3 ± 2.0 years, with age range from 17 to 27 years. Majority of the students’ responses indicated that they favored various aspects of TBL. Mean scores for the three TBL-SAI subscales, accountability, preference for lecture or TBL, student satisfaction, were 31.3 ± 3.3, 54.3 ± 7.4, 31.2 ± 4.4 respectively. All the three subscales of TBL-SAI attained scores well above the threshold favoring TBL. Majority of the students preferred online TBL compared to paper based TBL. No statistically significant results were found in logistic regression analyses carried out to identify characteristics associated with preference for TBL. Conclusion: Pharmacy students preferred TBL over traditional lecture-based teaching. Furthermore, they preferred the online mode of TBL as they found it to be more organized, student and environment friendly compared to paper based TBL.
Keywords: Team-Based Learning; Pharmacy; Online; Perception; United Arab Emirates